The Effectiveness of Couples’ Relationship Enrichment Training with Emotion-Focused Approach on Fear of Intimacy and Insecure Attachment Styles - Kiadarbandsari, Zohreh; Mirza Hosseini, Hasan; Zargham Hajebi, Majid (International Journal of Applied Behavioral Sciences, 2022)
Background and Aim:Marital infidelity is a traumatic interpersonal issue that can lead to cognitive, emotional, and behavioral symptoms in the victim. Therefore, this study aimed to investigate the effectiveness of couples’ relationship enrichment training with the EFT, emotion-focused approach on fear of intimacy and insecure attachment styles among couples faced with spousal infidelity. Materials and Methods:The method of the study was a semi-experimental with pre-test, post-test, control group and with the follow-up phase. The statistical population of this study was all men and women faced with spousal infidelity in Tehran in 2019-2020.Throughconvenience sampling method, 40 people were selected and randomly divided into an intervention group by training couples’ relationship enrichment with an emotion-focused approach and a control group. The experimental group underwent 8 sessions of 90 minutes of training to enrich couples’ relationships with an emotion-focused approach and the control group stayed on the waiting list. Data were collected based on an attachment styles questionnaire and fear of intimacy questionnaire. Multivariate covariance analysis test was used to eliminate the effect of pre-test using SPSS software. Results:The results showed that emotion-focused training affected the scores of insecure attachment styles (P<0.01) and fear of intimacy (P<0.01). The results also showed that the method of training was to enrich couples’ relationships with an emotion-focused approach in the follow-up phase. Conclusion:It can be concluded that the intervention on training couples’ relationship enrichment focused on the emotion-focused approach is an effective model in women and men affected by spousal infidelity and can be used as one of the therapeutic or educational methods in couple therapy programs